A Pilot Genome-Wide Association Study in Postmenopausal Mexican-Mestizo Women Implicates the RMND1/CCDC170 Locus Is Associated with Bone Mineral Density. (3rd August 2017) - Villalobos-Comparán, Marisela; Jiménez-Ortega, Rogelio F.; Estrada, Karol; Parra-Torres, Alma Y.; González-Mercado, Anahí; Patiño, Nelly; Castillejos-López, Manuel; Quiterio, Manuel; Fernandez-López, Juan Carlos; Ibarra, Bertha; Romero-Hidalgo, Sandra; Salmerón, Jorge; et al.
Abstract : To identify genetic variants influencing bone mineral density (BMD) in the Mexican-Mestizo population, we performed a GWAS for femoral neck (FN) and lumbar spine (LS) in Mexican-Mestizo postmenopausal women. In the discovery sample, 300, 000 SNPs were genotyped in a cohort of 411 postmenopausal women and seven SNPs were analyzed in the replication cohort (n = 420 ). The combined results of a meta-analysis from the discovery and replication samples identified two loci, RMND1 (rs6904364, P = 2.77 × 10 − 4 ) and CCDC170 (rs17081341, P = 1.62 × 10 − 5 ), associated with FN BMD. We also compared our results with those of the Genetic Factors for Osteoporosis (GEFOS) Consortium meta-analysis. The comparison revealed two loci previously reported in the GEFOS meta-analysis: SOX6 (rs7128738) and PKDCC (rs11887431) associated with FN and LS BMD, respectively, in our study population. Interestingly, rs17081341 rare in Caucasians (minor allele frequency < 0.03) was found in high frequency in our population, which suggests that this association could be specific to non-Caucasian populations. In conclusion, the first pilot Mexican GWA study of BMD confirmed previously identified loci and also demonstrated the importance of studying variability in diverse populations and/or specific populations.